The Determinant of Consumers Socio-Economic Attributes on Their Choices of Environmental Friendly Furniture style. - Karuna Kwangsawat; Yanin Rugwongwan (My University, 2017)
This article presents the determinant of consumers' socio-economic including personality, attitudes, lifestyle and the physical characteristics of the residence. That determines the consumer's demand for environmentally friendly furniture. This is a test of the demand for different types of furniture. According to economic conditions consumer society. The research found that overall style of furniture requirements. The consumers demand modern style furniture, western style, use natural materials to produce, high technology in production and the furniture is cool shade is moderate. The design should take into account the socio-economic conditions of each consumer group. To serve as guidelines for the environmentally friendly design furniture that is suitable to the demand of consumers.
Keywords: Environmentally Friendly; Consumer Demand; Consumer behaviour; Global socioeconomic and cultural dynamics